Evaluation of Rational Antibiotic Use in Non-Pneumonia ARI Disease Patients in the Working Area of Health Center "X" in Mining Area PT. ANTAM, Tbk Pomalaa Subdistrict - Hartati , Dwi Ayu; Risky, Sartini; Kamalia, Laode; Tonapa, Hasrul; Aisyiah Rizal, Nurul (Waluya The International Science of Health Journal, 2022)
136 Introduction: Infection of the airways is a common disease in the community. Most respiratory infections are caused by infections, but can also be caused by installation of organic materials or chemical vapors and inhalation of dust materials containing allergens. The main effects of dust on workers are both acute lung disorders and chronic physiological dysfunction, eye irritation, sensory irritation, and accumulation of harmful substances in the body. This study is intended to find out the rigors of antibiotics in cases of non-pneumonia airway infection disease in the working area of health center "X" in the mining area of PT. Antam Tbk Pomalaa Subdistrict June-December 2021 period. Method: Data retrieval is done descriptively by taking secondary data in the health center "X" mining area pt. Antam Tbk Pomalaa Subdistrict. The maximum value of antibiotics in ARI non-pneumonia disease is the maximum limit set by the health department, which is 20%. Result: The study there were 230 patients affected by non-pneumonia ARI disease in health center "X" mining area PT. Antam Tbk Pomalaa Subdistrict. Conclusion: The use of antibiotics in ARI non-pneumonia in health center "X" Pomalaa subdistrict is rational.